Fabrication in Mazahib: تلفیق فی المذہب - Ahmed, Sheraz; Baloch, Dr. Abubakar (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
It is obligatory necessary for a Muslim to follow one of the jurisprudential religions. However, in times of need or difficulty in a problem adoption of another religion is called Talfiq. Literally, the combination of two things is called Talfiq. Technically, it refers to the adoption of the opinion or religion of another mujtahid in any issue is Tafliq. In the literal sense of the word, Talfiq is common; however, here it is used for the adoption of another Mujtahid’s opinion. A common man can never be allowed to adopt the opinion of another religion. The purpose of preventing them from doing so is to prevent religion from becoming a means of following the desires of the psyche. Rather, this debate is about those who have the ability to issue fatwas on non-religion. A researcher mufti should find the best possible solution to the problems that arise remaining within his own religion. But if no solution is possible, he should find a solution to the problem while keeping in view the conditions (which will be discussed in detail in the following pages). The Talfiq is added to issues that are skeptical and ijtihadi Issues that are definite and the requirements are part of the religion or make Haraam to Halal or Halal to Haraam are not added to Talfiq. There are three possible ways to consider of Talfiq: (1) It should be declared absolutely permissible. (2) It should be declared absolutely illegal. (3) It should be allowed as per necessity and expediency. In the following lines, the same rules of consideration have been reviewed.